PENGARUH ORGANIZATIONAL FACTORS TERHADAP PENGUKURAN KINERJA PADA PEMERINTAH DAERAH DI INDONESIA - Lovina Eka Putri (2020)
This research was determine the effect of organizational factors, which are metric difficulties, technical knowledge, management commitment, legislative mandate and resources on performance measurement. The sample was the Head of Subdivision Planning of Bekasi City Government. Sampling was taken by probability sampling method. The samples used in this research amounted to 44 samples of the Head of Subdivision Planning of Bekasi City Government. The analysis technique used is Structural Equation Modelling, using the Smart Partial Least Square version 3.0. The results of this study indicate that Legislative Mandate and Resources significantly influence Performance Measurement. Metric Difficulties, Technical Knowledge and Management Commitment does not significantly influence Performance Measurement.